A Comparative Study of CCA Treatment of Tree Guard Poles of Eucalyptus Hybrid by Sap-displacement and Boucherie Processes - Sharma, S. N.; Krishna Rao, P. V.; Srinivaan, V. V. (Indian Forester, 1988)
The result of experiment carried out on treatment of freshly felled tree guard poles of Eucalyptus hybrid with CCA by the sap-displacement and Boucherie processes have been described in this paper.